Russian Zavrelia Kieffer (Diptera: Chironomidae), with the description of two new species - Zorina, Oksana V. (Zootaxa, 2008)
Two new species of Zavrelia Kieffer, Z. elenae sp. n. and Z. pseudopentatoma sp. n. from the Russian Far East are described and figured as male, pupa and larva. The generic diagnosis is emended to accommodate the new species. Keys to the males, pupae and larvae of the Russian Zavrelia species are given.